Type, form & function : a handbook on the fundamentals of typography - Tselentis, Jason (Rockport Publishers, 2011)
'Typology' is a useful, comprehensive typography resource that both students and professional designers should have in their library. It looks at the influences of modern typography and symbols going back through time and examines certain type treatments and movements in design and logo types.